FACTORS ASSOCIATED WITH TUMOR RECURRENCE IN STAGE 1 BLADDER TRANSITIONAL CELL CARCINOMA IN SARDJITO HOSPITAL YOGYAKARTA - putra, donny eka; Utomo, Trisula (Indonesian Urological Association, 2016)
Objective: This study is assigned to evaluate factors associated with tumor recurrence in patients with superficial transitional cell carcinoma (TCC) of bladder in Sardjito General Hospital Yogyakarta. Material & methods:A prospective observational study design is conducted to evaluate patients with T1 TCC of bladder between 2011 and 2012. Inclusion criteria was patients with T1 TCC of bladder from pathological report. The independent variables are ages, hemoglobin, albumin, creatinine level, urine cytology, tumor grade, tumor diameter, number of tumor, and intravesical chemotherapy. The outcome measure is tumor recurrence during cystoscopy at 3, 6, 9, and 12 month after first resection. This study used chi-square and logistic regression analysis as statistical methods with p < 0.05 and a = 5% are considered significant. All analyses were performed with SPSS statistical software, version 20.0. Result: Sixty-two patients were participated in this study with mean age 60.62 ± 12.15 years. There were 32 patients (51.6%) who had tumour recurrence during first year that need to be resected. Of these patients, 9 patients (14.5%) had tumour recurrence more than one time during first year. In multivariate analysis, factors associated with tumour recurrence were tumour grade (p = 0.041, CI = 0.008-0.908), number of tumor (p = 0.003, CI = 0.003-0.293), and intravesical chemotherapy (p = 0.022, CI = 0.015-0.719). Conclusion: Degree of tumor differentiation, number of tumor and intravesical chemotherapy are factors affecting recurrence of stage 1 transitional cell carcinoma of the bladder.